KERAGAMAN GENETIK CUCUMBER MOSAIC VIRUS ASAL TANAMAN TAPAK DARA, NILAM, KARUK, MELATI, DAN KUMIS KUCING - NFN Miftakhurohmah; Rita Noveriza; Maya Mariana (Buletin Penelitian Tanaman Rempah dan Obat, 2020)
Cucumber mosaic virus (CMV) symptoms are found in Catharanthus roseus, patchouly (Pogostemon cablin), cubeb (Piper chaba), Jasminum sambac and Java-tea (Orthosiphon aristatus); however, their genetic characterization has not been studied. The study aimed to molecularly characterize the CMV isolates from Catharanthus roseus, patchouly, cubeb, Jasminum sambac and Java-tea. Disease plant samples showing mosaic and yellow mosaic symptoms were collected from Petak Pamer Garden, ISMCRI, Bogor. Molecular characterization was carried out by reverse transcription-polymerase chain reaction (RT-PCR) assay using a specific primer of CMV coat protein gene and DNA sequenced. Sequence analysis was performed using the BLAST, Bioedit, Genedoc, Mega 5 programs. The RT-PCR technique succeeded in amplifying a DNA band measuring 650 bp, according to the prediction of the primary design.  BLAST analyses revealed that all of these CMV isolates belonged to subgroup IB. Nucleotide sequence homology of CMV from C. roseus, patchouly, P. chaba, and J. sambac, were more than 95.00%. Based on the phylogenetic tree, these four isolates were closely related to CMV isolate from Japan (AB070622). Homology of the nucleotide sequence of CMV from Java-tea with the other four isolates was below 95.00%. This isolate clustered with CMV isolate from Indonesia (AB042294) and was separated with another four isolates according to the phylogeny tree. In the amino acid sequence alignment, Java-tea isolates had five different amino acids compared to the other four isolates. This result indicates the possibility of CMV transmission between patchouly, Java-tea, C. roseus and J. sambac, so it must be anticipated to prevent its spread.